Do Chinese firms benefit from government ownership following cross-border acquisitions? - Tu, Wenjun; Zheng, Xiaolan; Li, Lei; Lin, Zhiang (John) (2021)
Chinese firms’ increasing cross-border acquisitions (CBAs) in recent years seem to challenge the explanatory power of received theories of multinational enterprise (MNE) due to their relatively unique characteristics and the active role of the Chinese government. In this study, we seek to revisit and contextualize the OLI paradigm in conjunction with the institution-based view and examine how Chinese firms’ post-CBA long term performance is associated with government ownership. Our study shows that Chinese firms with more government ownership demonstrate better post-CBA long term performance. However, the above relationship is differentially moderated by such firm-level boundary conditions as political connections and financial slack, and the country-level institutional boundary conditions (i.e., the host country formal institutions and the home-host country cultural distance). We discuss our findings in detail and explore theoretical and practical implications for both Chinese firms and other emerging economy (EE) firms.